Increased natural killer activity does not prevent progression of experimental kala-azar - Sartori, Alexandria [UNESP]; Kaneno, Ramon [UNESP]; Baruzzi, Nelson [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP] (FapUNIFESP (SciELO), 1999)
Kala-azar is the visceral form of leishmaniasis and it is caused by intracellular parasites from the complex Leishmania donovani. Golden hamster (Mesocricetus auratus) infected with Leishmania donovani develop a disease very similar to human Kala-azar. There is conspicuous hipergammaglobulinaemia and their T cells do not respond to stimulation with parasite antigens. We used this experimental model to evaluate the natural killer (NK) activity during the initial phase of the disease. Outbred hamsters infected by intravenous route with 5.106 amastigotes of L. donovani 1S showed a concurrent increase in the spleen weight and in the spleen cell number. Using the single cell assay we detected a significant increase in the percentage of NK effector cells on the 4th day of infection. Imprints from spleen and liver showed at days 14 and 28 a significant increase in the parasite burden. These results show that the increased NK activity in the beginning of the infection was not able to restrain the progression of the disease in this experimental model.
Keywords: Kala-azar; Leismania donovani; Natural killer activity; animal; disease course; disease model; female; hamster; immunology; Leishmania donovani; liver; lymphocyte count; lymphocyte subpopulation; natural killer cell; parasitology; spleen; visceral leishmaniasis; Animals; Cricetinae; Disease Models, Animal; Disease Progression; Female; Killer Cells, Natural; Leishmaniasis, Visceral; Liver; Lymphocyte Count; Lymphocyte Subsets; Spleen